Reliability of internet sources in geography: Case study of mountains Studena and Žaračka, Serbia - Lukić Tamara; Bubalo-Živković Milka; Đerčan Bojan (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
Jovan Cvijić said that geography is learned on foot. Besides fieldwork, the modern studies imply the usage of various software packages, as well as the data sources available from the Internet. All the data acquired from the Internet need to be carefully checked, unless they are retrieved from the websites of the established formal institutions (Government, Institutes, and Offices). Very often the Internet information may be in the form of data which should be additionally processed by using mathematical and statistics methods. Possibilities for Internet usage will be shown through presentation of the relief characteristics of the mountains Studena and Žaračka, which belong to Kopaonik system. They make a connection between Mt. Goč and Mt. Stolovi in the north and the massif of Mt. Željin and Mt. Kopaonik in the south. Taking into consideration that Mt. Studena and Mt. Žaračka were not previously studied by geographers, this paper is the contribution to the knowledge on these mountains. [Projekat Ministarstva nauke Republike Srbije, br. 176020]